Analyzing the Arm Muscular Strength of Rugby Athlete in Banten - Budiono, Agus; Lanos, Muhsana El Cintami; Kristina, Putri Cicilia (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2024)
This study aimed to analyze the arm muscle strength of rugby athletes in Banten. The method of measuring arm muscle strength involved using a gripper dynamometer. The research sample consisted of 30 rugby athletes who were actively training in Banten. Data were collected through the use of the gripper dynamometer to measure arm muscle strength and were analyzed using descriptive statistical techniques. The research results revealed significant variations in arm muscle strength among the rugby athletes in the sample. These findings highlight the diversity in physical strength within the group and provide valuable insights for coaches. Such insights can inform the development of more tailored and effective training programs to enhance arm muscle strength and overall performance in rugby athletes. Additionally, the study underscores the importance of regular strength assessments to monitor progress and adjust training regimens accordingly.